2006
DOI: 10.1007/s00330-006-0504-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow changes in beta-thalassemia major: quantitative MR imaging findings and correlation with iron stores

Abstract: The purpose of this study is to describe the MR imaging features of bone marrow in beta-thalassemia major and investigate their relation to ferritin, liver and spleen siderosis. Spinal bone marrow was prospectively assessed on abdominal MR studies of 40 transfused beta-thalassemic patients and 15 controls using T1-w, Pd, T2*-w Gradient Echo (GRE) and T1-w turbo Spin Echo (TSE) sequences. Signal intensity (SI) ratios of liver, spleen and bone marrow to paraspinous muscles (L/M, S/M, B/M respectively) and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
4
12
1
Order By: Relevance
“…In contradistinction, we documented a weaker correlation between bone marrow R 2 without fat suppression and ferritin (r=0.49) and no correlations between bone marrow, hepatic and pancreatic R 2 values without fat suppression. A previous study of our group with a larger number of patients with β-thalassemia revealed only a moderate correlation between bone marrow R 2 values and ferritin, splenic and hepatic R 2 values, but not with pancreatic R 2 values [18], whereas other studies [20,25] did not document statistically significant correlations between bone marrow, hepatic and pancreatic siderosis, estimated with the T2, T2⁎ or SIR methods.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…In contradistinction, we documented a weaker correlation between bone marrow R 2 without fat suppression and ferritin (r=0.49) and no correlations between bone marrow, hepatic and pancreatic R 2 values without fat suppression. A previous study of our group with a larger number of patients with β-thalassemia revealed only a moderate correlation between bone marrow R 2 values and ferritin, splenic and hepatic R 2 values, but not with pancreatic R 2 values [18], whereas other studies [20,25] did not document statistically significant correlations between bone marrow, hepatic and pancreatic siderosis, estimated with the T2, T2⁎ or SIR methods.…”
Section: Discussioncontrasting
confidence: 75%
“…To the best of our knowledge, no previous study has applied fat suppression in multiecho sequences for R 2 or R 2 ⁎ relaxometry for iron overloaded tissues well known to contain significant amounts of fat [18][19][20][21][22][23][24][25]. Schwenzer et al [32] have been the only group that had applied fat suppression in a multiecho gradient sequence for T2* calculation in a large cohort of 129 healthy subjects, and they found a significant correlation between hepatic T2* and ferritin (r=0.62) but no correlation between pancreatic T2* and ferritin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a few imaging studies decribed that the main findings of bone marrow in thalassemic patients were red marrow hyperplasia and marrow haemosiderosis [14,15]. Recently, Drakonaki et al [24] had prospectively assessed the spinal bone marrow signal intensity ratio on abdominal MR studies of 40 transfused beta-thalassemic patients and correlated with ferritin values. In the current study, we focused on the MR assessment of femoral marrow in beta-thalassemic patients and its capacity to predict HSCT outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the lack of biopsies due to ethical reasons. However, MR imaging is considered accurate for iron quantification even more than biopsy, due to the examining of the entire organ [24] and sensitivity of FFE images with long TE to slight iron deposits [18]. Iron and trabecular bone and firbrotic tissue could produce low signal intensity in both the gradient echo and TSE sequences [26].…”
Section: Discussionmentioning
confidence: 99%